FORMULASI DAN UJI AKTIVITAS ANTIBAKTERI SEDIAAN GEL EKSTRAK DAUN SELEDRI (Apium graveolens L) TERHADAP BAKTERI Pseudomonas aeruginosa - Suci Della; Muhammad Yunus; Erida Novriani (Universitas Imelda Medan, 2026)
Formulation and Antibacterial Action Assessment of Celery Leaf Extract Gel (Apium graveolens L. ) Against Staphylococcus aureus and Pseudomonas aeruginosa Bacteria Celery (Apium graveolens L.) is a plant recognized for its ability to fight bacteria because of substances like flavonoids, saponins, and tannins, which offer promising natural antibacterial alternatives. This study aimed to create a gel from celery leaf extract and test its antibacterial properties against Staphylococcus aureus and Pseudomonas aeruginosa. The celery leaves were extracted using the maceration method with 96% ethanol, achieving a yield of 17.25%. Four distinct gel formulations were produced with varying levels of extract: 0% (F0), 5% (F1), 10% (F2), and 15% (F3), utilizing HPMC as the gel base. Evaluations of the physical properties, which included sensory testing, uniformity, pH, spreadability, and viscosity, showed that all formulations met the quality criteria for gel products. The pH values ranged from 6. 63 to 6. 81, the spreadability was recorded between 5-6 cm, and the viscosity varied from 15,567 to 18,325 cPs. The antibacterial effectiveness test on Staphylococcus aureus, conducted through the disc diffusion method, revealed inhibition zones of 9.2 mm (moderate), 10.3 mm (moderate), and 11.48 mm (strong) at concentrations of 2.5%, 5%, and 10%, respectively. These results indicate that the gel made from celery leaf extract shows antibacterial effects against Staphylococcus aureus, with the highest efficacy observed at a concentration of 10%.